Measuring the Success of Smart Villages: Empowering Communities through Digital Skill Development - Darusman; Annisa, Yulia; Putra Fahreza, Ilza (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This research is motivated by the digital divide between urban and rural areas in Riau Province, especially in the transformation of villages into Smart Villages. The focus is on measuring the impact of digital skills development on three pillars: Smart People, Smart Economy, and Smart Living. Using a quantitative survey method, data were collected from 80 respondents using the Quota Sampling technique in four villages in Kampar Regency that have participated in digital skills training since 2021. Multivariate regression analysis was conducted to examine the relationship between digital skills and access to employment, entrepreneurship, and quality of life. The results showed that digital skills training contributed positively to improving access to employment (Smart People). However, its impact is still influenced by other factors such as access to relevant job markets. In the Smart Economy aspect, although field observations showed an increase in local entrepreneurship, regression analysis indicated that digital skills had a very small impact on entrepreneurship improvement, likely due to more dominant factors such as technology and innovation. The conclusion of this study reveals that digital skills development has a positive impact on transforming villages into Smart Villages. Still, it requires better infrastructure support and broader community involvement to ensure equitable benefits.